EDUCAÇÃO TEOLÓGICA E EDUCAÇÃO AMBIENTAL: HÁ LUGAR NOS ESPAÇOS DA EDUCAÇÃO TEOLÓGICA NO BRASIL PARA A RESPONSABILIDADE AMBIENTAL NA PERSPECTIVA DA MISSÃO INTEGRAL? - MARINGOLI, ÂNGELA (2016)
Theological Education is a product of Christian culture that with its dogmas, doctrinal and theological views permeates the basic Bible teachings. It has been consolidated along the lines of the many ambiguities and social transformations which societies and Christianity suffered. In Brazil, the same process has happened. The thesis that we defend is that for nowadays the evangelical Theological Education may revise their teaching programs in Missiology-related disciplines as well as in Sociology, Anthropology, Ethics and Citizenship and others, with the logic of environmental education knowledge, considering the theological landmarks of Integral Mission. Environmental education is also sometimes understood as political education because it is part of the transforming actions of the society it is in, transforming it into a sustainable society. Environmental Education, which includes the study of biodiversity, sustainable development, the laws against environmental crimes and others, through its knowledge, has the ability to prepare individuals and groups for the full exercise of citizenship. Sociological aspects of Environmental Education establish relationship with the daily life of citizens for the purpose of producing a process of continuous growth and also of awareness with respect to environmental events. Therefore, this research will promote an assessment of receiving the Environmental Education knowledge in colleges and Brazilian theological seminaries in order to formulate a program content of Missiology to meet the needs of society and Integral church mission. For this, we will analyze comparatively Curriculum Matrices, the Menus, and the Work of Completing Courses of colleges and seminaries in the 2010 to 2014 five schools: Baptist Theological College of São Paulo, School of Mackenzie Presbyterian Theology, both in the city of Sao Paulo Theological Southern College American, Londrina in Paraná, the Faetad - Faculty of Theological Education of the Assemblies of God in São Paulo and the CEM, the Evangelical Mission Centre which has its headquarters in Viçosa in Minas Gerais. From this analysis indicate content and practical sketches in the field of Teoambientologia